Table of Content - - (Journal of Humanities & Social Sciences, 2025)
Table of Content: 1. Arabic calligraphy in the face of digitization: A Reading on Function, Aesthetics and Identity Dr. Benadda Hadj Mohammed 2. The Extent of Benefiting from Artificial Intelligence Technique in Creating Designs Inspired by Al-Asiri Cat Ornaments to Enrich Clothing Accessories Ms. Walaa Mohamed Abdelaziz 3. Social Aspects of India Through the Journey of Ibn Battuta, Entitled Tuhfat al-Nuzzar fi Ghara’ib al-Amsar wa ‘Aja’ib al-Asfar (d. 779AH / 1377 AD) Ms. Manal Hilal Mutawaq 4. Geographical distribution of diabetes patients in Kingdom of Saudi Arabia (2019) with a global overview of diabetes prevalence Dr. Ayedh Abdullah Al-Qahtani 5. Analytical of the press discourse of the Israeli war on Gaza 2023 (Al-Aqsa Flood) in the Palestinian newspapers. "Al-Quds Newspaper as a model" Asst-Prof. Ahmad A.I. Alshaqaqi 6. Transformations of aesthetic and health values associated with the body and their impact of social behavior (Field study at King Faisal University) Ms. Nourah Abdullah Alsalem ,Dr. Ahlam Alataa Mohammed 7. The Negative Impact of Some Influencers’ Content on Social Media in Mauritania A Descriptive and Analytical Study Mr. Ahmed Sidi